Peningkatan Kualitas Pengajaran Akuntansi dan Simulasi Uji Kompetensi Akuntansi Guru SMK Puragabaya Kota Bandung - Hastuti Hastuti; Arry Irawan; Mia Rosmiati; Sulistia Suwondo; Sumiyati Sumiyati; Benny Barnas (LPPM UNINUS, 2020)
The community service program is aimed at improving the quality of accounting teaching for accounting teachers and providing a simulation of accounting competency tests. The method of implementing the activity is carried out with focus group discussions, accounting training and accounting competency test simulations. The training material adopted the competency units issued by LSP-TA and was in line with SKKNI. Participants in this program are 18 accounting teachers who participated in this activity from beginning to end. Program evaluations have been carried out to measure program effectiveness. Evaluation is carried out on aspects of training material and aspects of organizing activities. In the material aspect, the evaluation is done by evaluating the results of an accounting competency test simulation. The assessment is carried out by following the accounting competency test assessment pattern used by LSP-TA. Evaluation of the implementation of activities carried out to evaluate the training material, resource persons, facilities / logistics during the activity. In addition, participants are also entitled to provide advice and input on the implementation of activities